2017
DOI: 10.1093/bioinformatics/btx496
|View full text |Cite
|
Sign up to set email alerts
|

MusiteDeep: a deep-learning framework for general and kinase-specific phosphorylation site prediction

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
207
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(221 citation statements)
references
References 30 publications
2
207
0
Order By: Relevance
“…As underlined by a recent review [7], most of the phosphoproteome is uncharted: more than 95% of reported human phosphosites have no known kinase or associated biological function. 45 To identify a phosphorylation site on a protein sequence, several computational methods have been proposed earlier [13,15,[17][18][19][20][24][25][26][27][28][29][30][31][32]. Since these methods can also provide kinase specific predictions, they can be used to predict associated kinases of a known phosphosite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As underlined by a recent review [7], most of the phosphoproteome is uncharted: more than 95% of reported human phosphosites have no known kinase or associated biological function. 45 To identify a phosphorylation site on a protein sequence, several computational methods have been proposed earlier [13,15,[17][18][19][20][24][25][26][27][28][29][30][31][32]. Since these methods can also provide kinase specific predictions, they can be used to predict associated kinases of a known phosphosite.…”
Section: Introductionmentioning
confidence: 99%
“…The application of such tools is limited to kinases for which a substantial number of target phosphosites are available for training. For 55 example, MusiteDeep [20], uses deep learning to predict binding sites for kinases, and it exclusively focuses on kinase families with at least 100 experimentally verified phosphosites. Recently, the use of phosphorylation data to predict kinases has been proposed, but these methods also require knowledge of target sites for a kinase to make predictions for that kinase [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, for a given kinase family, a separate machine learning model was built to capture the unique pattern embedded in the substrate sequences of this family. Many successful applications belong to this family-specific category, such as NetPhosK (Neural Networks) [4] , KinasePhos (Hidden Markov Models) [5], PhosPhoPICK (Bayesian Networks) [6], PhosphoPredict (Random Forests) [7], Musit-eDeep (Convolutional Neural Network) [8], and many others [9][10][11][12][13]. An important prerequisite of these family-specific methods is the availability of a sufficient amount of high-quality data for model training.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is often not the case: a majority of kinase families have less than 30 experimentally verified phosphorylation sites. As a result, previous studies have to choose to build family-specific models for well-characterized kinase families (typically <10 families) with abundant training data [7,8,14]. For those less-studied kinase families, using the family-specific approach fails to provide satisfactory performance due to the lack of sufficient training data.…”
Section: Introductionmentioning
confidence: 99%